Vibration Transfer Function of Railway Vehicle System and its Spatial Coherence Under Vertical Track Irregularity Conditions - Peng Lu; Xi Wang; Yu Hou (Chinese Journal of Mechanical Engineering)
Abstract Current research on rail vehicle system vibrations primarily relies on numerical methods, with vibration transfer functions commonly derived through data fitting. However, the physical mechanisms underlying these vibrations are not well understood. To clarify the vibration transfer function and its characteristics, four basic input vectors are defined, and an analytical method is proposed. The vibration transfer functions of the vehicle system are solved, and their spatial coherence is analyzed. The results show that there are two spatial scales and four coherent modes in the vehicle system. The track irregularity wavelengths are combined with two spatial scales to alter the proportions of basic input vectors and then show the characteristics of spatial coherence. Four coherent modes are involved in wheel-rail force and primary suspension force; two coherent modes are involved in bogie vertical motion; and their dominant modes vary with the input frequency. On the other hand, the coherent modes involved in the bogie pitching motion and vehicle body motion are single and fixed over the whole range of frequency. This study presents an analytical method for the rapid solution of dynamic responses in vehicle systems and systematically analyzes the coherence behavior of vibration transfer functions with respect to tracking irregularity wavelengths.